GPCR Crystallization Using Lipidic Cubic Phase Technique - Yin, Xin; Xu, Henghao; Hanson, Michael; Liu, Wei (Current Pharmaceutical Biotechnology, 2014)
G protein-coupled receptors (GPCRs), a family of seven-transmembrane receptors, are among the most important drug targets with over half of all marketed drugs targeting the family. However, only a handful of easily druggable GPCRs are successfully targeted by pharmaceuticals. Efforts to shift this intensive focus to other, more recalcitrant GPCR targets will increasingly draw on new information such as structural details, which have until recently proven tremendously challenging to gather for this class of protein receptors due to the difficulties in obtaining diffraction-quality crystals. Recently, the development and application of lipidic cubic phase (LCP) technology has reduced one major hurdle for crystallization of GPCRs, with 22 unique receptors being structurally characterized from LCP grown crystals over the span of seven years. This review focuses on the technological improvements for LCP that have led to its successful utilization on the GPCR family, including the most recent combination of LCP with the X-ray free-electron laser that dramatically reduces requirements on crystal size, and holds significant promise for shortening timelines for structure determination and for accessing previously unattainable structures such as those of signaling complexes.
Keywords: G protein-coupled receptor (GPCR)